2018
DOI: 10.3892/ol.2018.8948
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic miR‑425‑5p is associated with cellular migration, proliferation and apoptosis in renal cell carcinoma

Abstract: An increasing number of studies have demonstrated the function of microRNAs (miRNAs) in the initiation and development of various types of cancer. Among them, miR-425-5p is proven to serve an important function in several types of cancer, including gastric, cervical cancer, and hepatocellular carcinoma. However, the function of miR-425-5p in renal cell carcinoma (RCC) remains unclear. In the present study, it was demonstrated that the expression level of miR-425-5p was upregulated in RCC tissues and cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Previous reports have indicated that miRNAs serve a regulatory role in cell proliferation, differentiation, apoptosis, migration and metabolism (12,24,25). Studies have revealed that enhanced expression levels of miR-425-5p exist in different types of cancer, which suggest that miR-425-5p may have multiple functions in the development of cancer (22,26). Studies previously demonstrated that miR-425-5p can promote invasion and metastasis in hepatocellular carcinoma, colorectal cancer and gastric cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that miRNAs serve a regulatory role in cell proliferation, differentiation, apoptosis, migration and metabolism (12,24,25). Studies have revealed that enhanced expression levels of miR-425-5p exist in different types of cancer, which suggest that miR-425-5p may have multiple functions in the development of cancer (22,26). Studies previously demonstrated that miR-425-5p can promote invasion and metastasis in hepatocellular carcinoma, colorectal cancer and gastric cancer (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Emerging evidence suggests that miRNAs are abnormally expressed in human cancers, 8,9 and can function as either tumor suppressors or oncogenes, depending on the target genes regulated. 8,9 miRNAs were also reported to modulate many essential cell behaviors including cell proliferation, invasion, and apoptosis. 8,9 miR-152 is a member of the miR-148/152 family that shows reduced expression patterns in various types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 miRNAs were also reported to modulate many essential cell behaviors including cell proliferation, invasion, and apoptosis. 8,9 miR-152 is a member of the miR-148/152 family that shows reduced expression patterns in various types of cancer. 10 miR-152 functions as a tumor suppressor by targeting genes in cancers including nasopharyngeal carcinoma, endometrial cancer, and ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…miR‐103 can reduce the phosphorylation of Yes‐associated protein (YAP), which is a regulator of the Hippo pathway and plays an important role in cell proliferation and tumour progression . miR‐425 has been suggested to be an oncogene in several types of cancer, including renal and hepatocellular carcinoma . The expression of miR‐140 is decreased in breast cancer stem cells (BCSCs), and miR‐140 acts as a tumour suppressor gene to inhibit tumour proliferation by regulating Wnt1 .…”
Section: Discussionmentioning
confidence: 99%
“…24 miR-425 has been suggested to be an oncogene in several types of cancer, including renal and hepatocellular carcinoma. 25,26 The expression of miR-140 is decreased in breast cancer stem cells (BCSCs), and miR-140 acts as a tumour suppressor gene to inhibit tumour proliferation by regulating Wnt1. 27 It has been reported that miR-185 expression is downregulated in some tumours and that upregulation of miR-185 expression significantly inhibits the growth, migration, and invasion of Ewing's sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%